A New iPhone Application for Voice Quality Assessment Based on the GRBAS Scale. (9th July 2020) - Kojima, Tsuyoshi; Hasebe, Koki; Fujimura, Shintaro; Okanoue, Yusuke; Kagoshima, Hiroki; Taguchi, Atsushi; Yamamoto, Hirotaka; Shoji, Kazuhiko; Hori, Ryusuke
Abstract : View Video S1 Laryngoscope, 131:580–582, 2021